(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The curriculum of the interrelated subjects is one of the curricula emanating from the process of curriculum development, which has been applied to social subjects in the secondary school grades, as geography, history and national education have been integrated into one subject called sociology, and it is known that any curriculum needs to follow up the extent to which it achieves the aims and their success and this requires an opinion poll in the conviction of teachers and teachers of this integration, so the current research aimed to poll the opinion of teachers of the departments of history and geography in the College of Education And teachers of the subject in the integration in order to know the percentage of support for the integration of curricula has been using a tool represented by a question addressed to the sample of the research included 40 teachers of the departments of geography and history and 180 teachers and schools distributed to the six directorates of education of the province of Baghdad and, after the application of the tool analyzed the data mathematically appeared appeared the percentage of teachers of the College of Education non-supporters of this curriculum 90%, while the percentage of teachers and teachers non-supporters 95%, and thus note the high percentage of non-supporters of this curriculum and rejectionists This indicates the weakness of this approach in achieving its aims, and in light of this result a set of recommendations and proposals were presented.